Effects of recirculation on leachate characteristics at landfills - Bilgili, MS; Demir, A; Özkaya, B (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2004)
In this study, the effects of leachate recirculation on landfill stabilization and leachate characteristics are determined for municipal solid wastes of Istanbul. Two test cells (C1 and C2) with the dimensions of 25 x 50 x 5 m are used for the experiments at Odayeri Sanitary Landfill, which is the largest landfill of Turkey. The overall amount of landfilled waste was approximately 11.000 tons and solid waste quantities were almost equal for each cell. Leachate was recirculated to one of the test cells (C2) periodically. Stabilization indicators, such as pH, chemical oxygen demand (COD) and sulphate (SO42-), were monitored in the leachate generated. The optimum pH values for methanogenic activities were reached rapidly by leachate recirculation. COD values are decreased to lower levels in a shorter time in C2 test cell. The decrease of the SO42- concentration in the C2 test cell could also be realized rapidly, because of the acceleration of decomposition processes by leachate recirculation. The results show that the moisture content is the most important parameter affecting the decomposition rates of the wastes.
Keywords: solid waste; landfill; decomposition; leachate; recirculation; leachate characteristics; MUNICIPAL SOLID-WASTE; ANAEROBICALLY DECOMPOSED REFUSE; Environmental Sciences & Ecology